The Impact of Humanoid Robots on Australian Public Libraries. Issue 2 (2nd April 2020) - Nguyen, Linh Cuong
ABSTRACT: 'Humanoid robots' or 'social robots' are an emerging generation of robots that have abilities to perceive their environment, recognise faces, read emotions and communicate with people. They have been introduced into Australian public libraries over the past few years but their impact on library practice has remained unknown. This research therefore aims to fill this gap. It explores the influence of these robots on Australian public libraries through the view of librarians and the experience of library clients. Ten in-depth individual interviews with librarians in Australian public libraries, who are directly involved in designing and running humanoid robot programmes, were carried out. Observations of interaction between library patrons and humanoid robots at five events in five public libraries were also conducted. Interview transcripts and field notes were analysed using a thematic analysis approach. The analysis revealed four themes describing the way humanoid robots impact Australian public libraries. Humanoid robots are considered as a community builder, a teacher, an aide, and a challenger. This research provides an evidence-based understanding that supports the research, planning and implementation of humanoid robot initiatives in Australian public libraries in order to enhance the experience of library user communities.